Linkage to HIV care and hypertension and diabetes control in rural South Africa: Results from the population-based Vukuzazi Study - Itai M. Magodoro; Stephen Olivier; Dickman Gareta; Olivier Koole; Tshwaraganang H. Modise; Resign Gunda; Kobus Herbst; Deenan Pillay; Emily B. Wong; Mark J. Siedner (Public Library of Science (PLoS), 2022)
Non-communicable diseases (NCDs) account for half of all deaths in South Africa, partly reflecting unmet NCDs healthcare needs. Leveraging existing HIV infrastructure is touted as a strategy to alleviate this chronic care gap. We evaluated whether HIV care platforms are associated with improved NCDs care. We conducted a community-based screening of adults in rural KwaZulu-Natal, collecting BP, HbA1c, and health services utilization data. Care cascade indicators for hypertension and diabetes mellitus were defined as: 1) aware, if previously diagnosed, 2) in care, if seeing a provider within last 6 months; 3) treated, if reporting medication use within preceding 2 weeks; and 4) controlled, if BP<140/90mmHg or HbA1c<6.5%. We fit multivariable adjusted logistic regression models to compare successful completion of each step of the care cascade for hypertension and diabetes between people with virally suppressed HIV and HIV-negative comparators. Inverse probability sampling weights were applied to derive population-level estimates. The analytic sample included 4,933 individuals [mean age 58.4 years; 77% female]. Compared to being HIV-negative, having suppressed HIV was associated with lower adjusted prevalence of being aware (-6.0% [95% CI: -11.0, -1.1%]), in care (-5.7% [-10.6, -0.8%]), and in treatment (-4.8% [-9.7, 0.1%]) for diabetes; but higher adjusted prevalence of controlled diabetes (3.2% [0.2-6.2%]). In contrast, having suppressed HIV was associated with higher adjusted prevalence of being aware (7.4% [5.3-9.6%]), in care (8.0% [5.9-10.2%]), in treatment (8.4% [6.1-10.6%]) and controlled (9.0% [6.2-11.8%]), for hypertension. Overall, disease control was achieved for 40.0% (38.6-40.8%) and 6.8% (5.9-7.8%) of individuals with hypertension and diabetes, respectively. Engagement in HIV care in rural KwaZulu-Natal was generally associated with worse diabetes care and improved hypertension care. While further work should explore how success of HIV programs can be translated to NCD care, strengthening of primary healthcare will also be needed to respond to the growing NCDs epidemic.